2020
DOI: 10.1111/ppc.12608
|View full text |Cite
|
Sign up to set email alerts
|

Caring behaviors, moral sensitivity, and emotional intelligence in intensive care nurses: A descriptive study

Abstract: Purpose: To evaluate the relationship of caring behaviors with moral sensitivity, emotional intelligence and descriptive characteristics in intensive care nurses.Method: Descriptive study. The sample of this study consisted of 156 nurses. The data were collected using introductory information form, caring behaviors inventory, moral sensitivity questionnaire, and emotional intelligence scale. The factors affecting caring behavior were determined using stepwise multiple linear regression.Finding: It was determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 34 publications
1
20
0
Order By: Relevance
“…In the study of Nasiripour, which investigated the effect of education on promoting moral sensitivity on nurses' care behavior in Ahvaz, a positive relationship was observed between moral sensitivity training and nursing care behavior [34]. in another study by Taylan et al in Turkey, moral sensitivity was a predictor of caring behaviors [35]. The current study demonstrated that the level of Moral Sensitivity in nurses, based on Moral Sensitivity's mean score, was moderate (62.06 ± 11.49) during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Nasiripour, which investigated the effect of education on promoting moral sensitivity on nurses' care behavior in Ahvaz, a positive relationship was observed between moral sensitivity training and nursing care behavior [34]. in another study by Taylan et al in Turkey, moral sensitivity was a predictor of caring behaviors [35]. The current study demonstrated that the level of Moral Sensitivity in nurses, based on Moral Sensitivity's mean score, was moderate (62.06 ± 11.49) during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…However, although investigation on self‐compassion and compassion competence creates momentum, limited literature has been conducted among nursing students, most especially in the Arab region. In addition, certain studies have been carried out on factors affecting nursing caring behaviour (Taylan et al, 2020 ; Malekzadeh et al., 2018 ), and no detailed investigation on the effect of self‐compassion on caring behaviour and compassion competence among nursing students has been conducted. To appraise and enhance the patient quality care rendered, exploring the self‐compassion of future nurses is meaningful.…”
Section: Background Of the Studymentioning
confidence: 99%
“…39 In studies with nurses, a negative correlation was found between depersonalization and self-efficacy by Alidosti et al 35 and between depersonalization and caring behaviors by Shen et al 30 On the other hand, emotion and moral sensitivity are high predictors for caring behaviors. 40 The results of this present study will contribute to the existing data in the literature by suggesting that depersonalization plays a negative mediator role in the positive relationship between nurses' caring behaviors and self-efficacy.…”
Section: Resultsmentioning
confidence: 51%